FIAC '96 : L'Année de la Corée. - Sang-Neung, Kwan; Young-Ho, Kim (Paris : FIAC, 1996)
Keon-Mo, Chung ; Kyu-Sun, Lee ; Ham Sup ; Ki-Won, Choi ; Jung-Tae, Suh ; Tai-Jung, Um ; Soo-Cheon, Jheon ; Ko Young-Hoon ; Se-Ok, Suh ; Moon-Sup, Shim ; Sang-Sook, Park ; Il-Ho, Lee ; Ou-Hi, Cha ; Ysan, Kim ; Dong-Chul, Ha ; Chong-hyun, Ha ; Kwan-Mo, Chung ; Seo-Bo, Park ; Duck-Hyun, Cho ; Keun-Byung, Yook ; Kang-So, Lee ; Hoon, Kwak ; Sung-Mook, Cho ; Ju-Hae, Yang ; Lee Doo-Sik ; Hyung-Woo, Lee ; Chang-Hyun, Ha ; Dong-Chin, Sohn ; Man-Lin, Choi ; Byong-Jong, Kim ; Won-Sook, Kim ; Young-Sung, Hwang ; Chung Il
biografie
FIAC '96 : L'Année de la Corée / The year of Korea, Espace Eiffel Branly, Paris, 2-7 October 96
Engels & Frans
boek
Keywords: Korea